PENERAPAN METODE MOORA DALAM PEMERINGKATAN STRATEGI DIGITAL MARKETING TIKTOK SHOP PADA PRODUK FASHION - fifin kumalasari; Rini Indriati, M.Kom; Erna Daniati, M.Kom (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
The growth of social commerce encourages fashion businesses to evaluate their digital marketing strategies in a more measurable manner. Barley Division is a local fashion brand that uses TikTok Shop as a medium for product promotion and sales. However, selecting the most effective strategy requires measurable data rather than relying only on intuition. This study applies the Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) method to rank TikTok Shop digital marketing strategies for fashion products. The research data were obtained through interviews, observations of marketing activities, and marketing performance documentation, and were then converted into a 0-100 rating scale. The alternatives analyzed include live streaming, product content, affiliate programs, flash sales, and influencers. The evaluation criteria consist of reach, engagement, conversion, and sales, with weights of 30%, 25%, 25%, and 20%, respectively. The analysis stages include constructing the decision matrix, normalizing the data, applying criterion weights, calculating optimization values, and ranking the alternatives. The results show that live streaming obtains the highest preference value of 0.4899, followed by flash sale at 0.4553, affiliate program at 0.4528, product content at 0.4198, and influencer at 0.4124. These results indicate that live streaming is the most effective strategy because it combines reach, direct interaction, and real-time purchase encouragement. This study provides a MOORA-based decision support model that can help business actors prioritize digital marketing strategies objectively and based on measurable data.